COMPARATIVE ANALYSIS OF THE WASTE MANAGEMENT SYSTEM EFFICIENCY IN SOME COUNTIES FROM ROMANIA AND POLAND - OANA TIRTOACA (IRIMIA); PRZYDATEK GRZEGORZ (Journal of Engineering Studies and Research)
In recent years, technology and innovation have also reached the field of waste. They provide an excellent opportunity to improve policies aimed at minimizing waste generation and achieving resource efficiency. However, the degree of introduction of innovative equipment and practices varies significantly from one territory to another. The comparative analysis carried out on within 5 years, showed noticeable changes in the counties in Romania and Poland initiated by the EU and national legislation which indicated an increase in the amount of waste recovered. However, the achieved efficiency of limiting the deposited waste was different at the level of exceeding 70 % and higher of 0.10 kg an average indicator of waste accumulation per capita in Bacau County. Two counties mainly difference composition of municipal waste with predominance of biodegradable waste (60 %) in Bacau County and glass waste (35 %) in Nowy Sącz County with raw material properties. Differences were also noticeable in the case of hygiene fees with exceed of average value 20 EUR in Nowy Sącz County. The gradual increase in the amount of recycled waste and covering all residents with hygiene services should be considered beneficial which indicates an improvement in environmental awareness.